Patellogastropoda and Vetigastropoda (Mollusca, Gastropoda) from the marine Jurassic of Patagonia, Argentina - Ferrari, Silvia Mariel (2014)
Gastropod faunas from the Early Jurassic (Late Pliensbachian–Early Toarcian) marine deposits of Chubut Province, Argentina, are described from Lomas Occidentales, Cerro La Trampa and Puesto Currumil localities, representing eight species, three of them new. These are Scurriopsis? sp., Chartronella gradata sp. nov., Calliotropis? sp., Pleurotomaria sp., Leptomaria sp., Hamusina? wahnishae sp. nov., Colpomphalus musacchioi sp. nov. and Jurassiphorus? cf. triadicus Haas. The gastropod assemblage reported here testifies paleobiogeographical connections with other coeval gastropod associations from the western Tethys. However, Chartronella, Hamusina and Jurassiphorus may represent survivors of Triassic associations, considering the ancient seaway from Peru as the most plausible hypothesis for biotic exchange of these faunas during the Late Triassic–Early Jurassic boundary. An abundant and diverse invertebrate fauna such as corals, echinoderms, cephalopods, brachiopods, bivalves and other gastropods found in association with the gastropods described here characterises a shallow marine environment for the gastropod-bearing rocks.